The Distributional Impact of Structural Reforms - Causa, Orsetta (OECD Publishing, 2016)
In a majority of OECD countries, GDP growth over the past three decades has been associated with growing income disparities. To shed some lights on the potential sources of trade-offs between growth and equity, this paper investigates the long-run impact of structural reforms on household incomes across the distribution, hence on income inequality. The paper builds on a macro-micro approach by combining recent macro-level estimates of the impact of structural reforms on macroeconomic growth with micro-level estimates of the impact of structural reforms on household incomes across the income distribution. It considers the sources of macroeconomic growth, by decomposing growth in GDP per capita into growth in labour utilisation and labour productivity. This allows for shedding light on the mechanisms through which growth and its drivers, including policy drivers, benefit household incomes at different points of the income distribution. Most structural reforms are found to have little impact on income inequality when the latter is assessed through measures that emphasise the middle class. By contrast, a higher number of structural reforms, in particular social protection reforms, are found to have an impact on income inequality and thus may raise tradeoffs and synergies between growth equity objectives when inequality is assessed through measures that emphasise relatively more incomes among the poor. This corresponds to higher degrees of inequality aversion
Keywords: Economics